Gastrointestinal bleeding and endoscopic findings in critically and non‐critically ill patients with corona virus disease 2019 (COVID‐19): Results from Lean European Open Survey on SARS‐CoV‐2 (LEOSS) and COKA registries. Issue 9 (15th October 2021) - Zellmer, Stephan; Hanses, Frank; Muzalyova, Anna; Classen, Johanna; Braun, Georg; Piepel, Christiane; Erber, Johanna; Pilgram, Lisa; Walter, Lorenz; Göpel, Siri; Wille, Kai; Hower, Martin; et al.
Abstract: Background: Corona virus disease 2019 (COVID‐19) patients are at increased risk for thromboembolic events. It is unclear whether the risk for gastrointestinal (GI) bleeding is also increased. Methods: We considered 4128 COVID‐19 patients enrolled in the Lean European Open Survey on SARS‐CoV‐2 (LEOSS) registry. The association between occurrence of GI bleeding and comorbidities as well as medication were examined. In addition, 1216 patients from COKA registry were analyzed focusing on endoscopy diagnostic findings. Results: A cumulative number of 97 patients (1.8%) with GI bleeding were identified in the LEOSS registry and COKA registry. Of 4128 patients from the LEOSS registry, 66 patients (1.6%) had a GI bleeding. The rate of GI bleeding in patients with intensive care unit (ICU) admission was 4.5%. The use of therapeutic dose of anticoagulants showed a significant association with the increased incidence of bleeding in the critical phase of disease. The Charlson comorbidity index and the COVID‐19 severity index were significantly higher in the group of patients with GI bleeding than in the group of patients without GI bleeding (5.83 (SD = 2.93) vs. 3.66 (SD = 3.06), p < 0.01 and 3.26 (SD = 1.69) vs. 2.33 (SD = 1.53), p < 0.01, respectively). In the COKA registry 31 patients (2.5%) developed a GI bleeding. Of these, the source of bleeding was identified in upper GI tract in 21 patients (67.7%) with ulcer as the most frequent bleeding source (25.8%, n = 8) followed by gastroesophageal reflux (16.1%, n = 5). In three patients (9.7%) GI bleeding source was located in lower GI tract caused mainly by diverticular bleeding (6.5%, n = 2). In seven patients (22.6%) the bleeding localization remained unknown. Conclusion: Consistent with previous research, comorbidities and disease severity correlate with the incidence of GI bleeding. Also, therapeutic anticoagulation seems to be associated with a higher risk of GI bleeding. Overall, the risk of GI bleeding seems not to be increased in COVID‐19 patients.